IMPlementation of An online Relatives' Toolkit for psychosis or bipolar (IMPART study): iterative multiple case study to identify key factors impacting on staff uptake and use - Fiona Lobban; Duncan Appelbe; Victoria Appleton; Julie Billsborough; Naomi Ruth Fisher; Sheena Foster; Bethany Gill; David Glentworth; Chris Harrop; Sonia Johnson; Steven H. Jones; Tibor Zoltan Kovacs; et al. (BMC, 2020)
Abstract Background Despite the potential of digital health interventions to improve the delivery of psychoeducation to people with mental health problems and their relatives, and substantial investment in their development, there is little evidence of successful implementation into clinical practice. We report the first implementation study of a digital health intervention: Relatives Education And Coping Toolkit (REACT), into routine mental healthcare. Our main aim was to identify critical factors affecting staff uptake and use of this online self-management tool for relatives of people with psychosis or bipolar. Methods A mixed-methods, theory-driven (Normalisation Process Theory), iterative multiple case study approach using qualitative analysis of interviews with staff and quantitative reporting of uptake. Carer researchers were part of the research team. Results In all, 281 staff and 159 relatives from Early Intervention teams across six catchment areas (cases) in England registered on REACT; 129 staff took part in qualitative interviews. Staff were positive about REACT helping services improve support and meet clinical targets. Implementation was hindered by: high staff caseloads and difficulties prioritising carers; perception of REACT implementation as research; technical difficulties using REACT; poor interoperability with trust computer systems and care pathways; lack of access to mobile technology and training; restricted forum populations; staff fears of risk, online trolling, and replacement by technology; and uncertainty around REACT's long-term availability. Conclusions Digital health interventions, such as REACT, should be iteratively developed, evaluated, adapted and implemented, in partnership with the services they aim to support, and as part of a long term national strategy to co-develop integrated technology-enabled mental healthcare. Implementation strategies must instil a sense of ownership for staff and ensure they have adequate IT training, appropriate governance protocols for online working, and adequate mobile technologies. Wider contextual factors including adequate funding for mental health services and prioritisation of carer support, also need to be addressed for successful implementation of carer focussed digital interventions. Trial registration Study registration: ISCTRN 16267685 .